ITIL 4 create, deliver and support (CDS) : your companion to the ITIL 4 Managing Professional CDS certification - Agutter, Claire (ITGP, 2021)
An excellent supplement to any ITIL 4 Create, Deliver and Support training course ITIL® 4 Create, Deliver and Support (CDS) - Your companion to the ITIL 4 Managing Professional CDS certification is a study guide designed to help students pass the ITIL® 4 Create, Deliver and Support module.